The added value of an internet-based intervention for treatment of aggression in forensic psychiatric outpatients—study protocol for a multicentre, mixed-methods randomized controlled trial - Hanneke Kip; Lisa Klein Haneveld; Saskia M Kelders (Digital Health)
Background Even though internet-based interventions have been used in treatment of forensic psychiatric outpatients for over 10 years, no robust effectiveness studies have been conducted in this complex branch of mental healthcare. Objectives To present the protocol of a study that investigates whether the addition of the internet-based intervention “Dealing with Aggression” to treatment as usual (TAU) leads to better treatment outcomes than TAU that is delivered solely in-person. Methods This study uses a multicentre mixed-methods randomized controlled trial (RCT) design, with four Dutch forensic outpatient organizations. Patients are included if they receive outpatient treatment for aggression. They will be randomized into an experimental condition, in which the intervention is added to TAU (n = 64), or a control condition, with only TAU (n = 64). Participants are assessed four times: at baseline (T0), halfway during the 10-week intervention (T1), after completing the intervention (T2), and after 3 months (T3). Primary outcome measure is self-reported aggression, other outcome measures are regulatory emotional self-efficacy and treatment readiness, the number of treatment sessions, and dynamic risk factors. Adherence to and engagement with the internet-based intervention will be investigated as predictors for effectiveness. Perceived effect and points of improvement are identified via semistructured interviews with patients and therapists. Discussion This will be the first study to investigate the effectiveness of an internet-based intervention in a forensic psychiatric outpatient sample. By means of the mixed-methods design and use of adherence and engagement as predictors, this study will answers questions about if, but also why and for whom this intervention works.